The Dynamics of the Islamic Religious Education Curriculum in Responding to Social and Technological Changes - Halwa Hasnia Noor (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Social change and technological development have significantly transformed the orientation, content, pedagogy, and implementation of the Islamic Religious Education curriculum. This study aims to analyze the dynamics of the Islamic Religious Education curriculum in responding to these changes, identify the major challenges and opportunities in its implementation, and formulate an adaptive-transformative conceptual framework. The study employed a qualitative approach using library research. Data were obtained from journal articles, academic books, policy documents, conference proceedings, and other relevant scholarly sources published mainly between 2015 and 2026. The data were analyzed through qualitative content analysis involving data condensation, thematic organization, comparative interpretation, and conclusion drawing. The findings indicate that the Islamic Religious Education curriculum has shifted from a predominantly normative and teacher-centered orientation toward a more contextual, integrative, competency-based, and learner-responsive model. Technological integration provides opportunities to expand access, enrich learning resources, strengthen digital literacy, and support interactive pedagogy. However, its implementation is constrained by unequal infrastructure, limited teacher readiness, institutional resistance, weak professional development, and ethical concerns related to misinformation, digital dependence, and the authority of religious knowledge. Based on the synthesis, this study proposes an adaptive-transformative framework consisting of six interconnected components: Islamic value foundations, contextual input, curriculum transformation, implementation capacity, integrated learner outcomes, and continuous evaluation and renewal. This framework positions Islamic values as the normative foundation for developing a curriculum that is socially relevant, technologically responsive, and spiritually grounded.